Impacts resulting from lack of knowledge about the reference system in geospatial information of Costa Rica: utility of metadata - Cedeño-Montoya, Bepsy; Moya-Zamora, Jorge (Revista Geográfica de América Central., 2018)
The maximum use of geospatial information depends on knowing the geodetic reference, which is essential to transform it into other references -if needed. In the specific case of Costa Rica, there is a significant amount of information that is linked to conventional datum Ocotepeque with their corresponding projections Lambert Costa Rica Norte (LCRN) and Lambert Costa Rica Sur (LCRS). And, in the last decade, the national information that has been generated is referenced to the official national datum CR05 and its corresponding map projection CRTM05 (Moya y Cedeño, 2016). The facilities offered by the Geographic Information Systems (GIS) –proprietary or free versions, are an excellent tool not only due to the speed in the different information processes, but also, and perhaps most importantly, because they give users a huge amount of results due to their multiple spatial analysis capabilities. However, it is essential that GIS are properly configured so that it is possible to extract as much information as possible and knowing that the initial information is properly georeferenced or that the prior georeference process is possible and correct. For this task, knowing the metadata is essential in order to know the origin of the information. The main purpose of this work is to show a lot of GIS users, the possible impacts resulting from the incorrect conversion process and coordinate transformation.